The Psychophysiological Experience of Solving Moral Dilemmas Together: An Interdisciplinary Comparison Between Participants With and Without Depression - Koskinen, Emmi; Tuhkanen, Samuel; Järvensivu, Milla; Savander, Enikö; Valkeapää, Taina; Valkia, Kaisa; Weiste, Elina; Stevanovic, Melisa (Frontiers in Communication, 2021)
Dyads with a depressed and a non-depressed participant (N=15) and two non-depressed participants (N=15) discussed a moral dilemma, during which the participants’ gaze direction and skin conductance (SC) were measured. Partner gazing occurred most frequently when a speaker took a strong stance toward saving a person in the dilemma, depressed participants however looking at their co-participants less often than non-depressed participants. The participants’ SC response rates were higher during responsive utterances expressing disagreement (vs. agreement) with co-participant ideas or suggesting that a person be sacrificed (vs. saved). We argue that a better understanding of the affective corollaries of human social interaction necessitates a balanced consideration of both contents of talk and behavioral patterns.